The Correlation Between Online Food Ordering and Nutritional Status among College Students in Surabaya - Ninuk Dian Kurniawati; Siti Nur Cahyaningsih; Andri Setya Wahyudi (Indonesian Journal of Community Health Nursing, 2021)
Introduction: The prevalence of overweight and obesity among adults has increased yearly in Indonesia. Online food ordering was believed to have a contribution to this condition as it shorten access to food. This study aimed to analyse the correlation between online food ordering and the nutritional status among college students in Surabaya.Method: This study used a descriptive correlational design with a cross-sectional approach. Samples were recruited using the convenience sampling technique; 388 college students at the B campus of Universitas Airlangga Surabaya were involved. The independent variable of this study was the intensity of online food ordering. While the dependent variable was the nutritional status among college students. A questionnaire and Food Frequency Questionnaire (FFQ) using google form which distributed online used as an instrument. Data were then analyzed by using Spearman Rho Test with level of significance (p<=0,05).Results: This study showed that online food ordering did not correlate with nutritional status (p=0.595). Most of food ordered online were high sugar, salt, and fat food.Conclusion: It is concluded that there is no relation between the intensity of online food ordering and nutritional status among college students.